Relevance of Pharmacogenomics to the Safe Use of Antimicrobials - Ann K. Daly (MDPI AG, 2023)
There has been widespread implementation of pharmacogenomic testing to inform drug prescribing in medical specialties such as oncology and cardiology. Progress in using pharmacogenomic tests when prescribing antimicrobials has been more limited, though a relatively large number of pharmacogenomic studies on aspects such as idiosyncratic adverse drug reactions have now been performed for this drug class. Currently, there are recommendations in place from either National Regulatory Agencies and/or specialist Pharmacogenomics Advisory Groups concerning genotyping for specific variants in MT-RNR1 and CYP2C19 before prescribing aminoglycosides and voriconazole, respectively. Numerous additional pharmacogenomic associations have been reported concerning antimicrobial-related idiosyncratic adverse drug reactions, particularly involving specific HLA alleles, but, to date, the cost-effectiveness of genotyping prior to prescription has not been confirmed. Polygenic risk score determination has been investigated to a more limited extent but currently suffers from important limitations. Despite limited progress to date, the future widespread adoption of preemptive genotyping and genome sequencing may provide pharmacogenomic data to prescribers that can be used to inform prescribing and increase the safe use of antimicrobials.